2006
DOI: 10.1021/ic060102b
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) Diimine Diacetylides:  Metallacyclization Enhances Photophysical Properties

Abstract: The synthesis, structural characterization, and photoluminescence properties of a new platinum(II) diimine complex bearing the bidentate diacetylide ligand tolan-2,2'-diacetylide (tda), Pt(dbbpy)(tda) [dbbpy = 4,4'-di-tert-butyl-2,2'-bipyridine], are described. In CH2Cl2, Pt(dbbpy)(tda) exhibits a strong visible charge-transfer absorption and broad emission centered at 562 nm. The photoluminescence quantum yield and excited-state lifetime are 0.52 and 2.56 mus, respectively, at room temperature. These paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
79
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 13 publications
11
79
0
Order By: Relevance
“…This blueshift in the absorption maximum is consistent with a metal‐to‐ligand/ligand‐to‐ligand charge‐transfer (ML/LL′CT) transition with significant involvement of the bipy π system in the LUMO . The methylene spacer decreases the electron‐withdrawing effect of the carboxyl/phosphonic ester group, and thus destabilises the LUMO and increases the HOMO–LUMO energy gap and consequently the energy of the corresponding absorption band.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This blueshift in the absorption maximum is consistent with a metal‐to‐ligand/ligand‐to‐ligand charge‐transfer (ML/LL′CT) transition with significant involvement of the bipy π system in the LUMO . The methylene spacer decreases the electron‐withdrawing effect of the carboxyl/phosphonic ester group, and thus destabilises the LUMO and increases the HOMO–LUMO energy gap and consequently the energy of the corresponding absorption band.…”
Section: Resultssupporting
confidence: 89%
“…All complexes displayed an electrochemically irreversible oxidation process between 0.67 and 0.73 V, attributed to the oxidation of the platinum acetylide subunit. The position and irreversible nature of this oxidation process is typical for platinum bipy acetylide complexes of this type . Little variation in oxidation potential between the four complexes implies that, as expected, the bipy ligands have little involvement.…”
Section: Resultsmentioning
confidence: 55%
“…The electrochemical measurements indicated that the oxidation processes are irreversible between +1.25 and +1.52 V, which can be attributed to the oxidation of the metal core (Table 5). 19, 24, 25 Such irreversibility is typical of Pt II complexes due to solvent coordination to the metal center upon oxidation, followed by a rearrangement of the ligands,26 which might also account for the lower current involved in the oxidation wave as compared to the reduction process. Complexes 1 and 4 showed reversibility in the reduction for scan rates above 0.5 and 2 V s −1 , respectively, whereas complexes 3 and 6 gave irreversible reductions between −1.7 and −1.9 V. The reduction of compounds 2 and 5 fall outside of the electrochemical window of the solvent/electrolyte, suggesting more negative reduction potentials (higher lying LUMOs) 27.…”
Section: Resultsmentioning
confidence: 99%
“…Youngs and co‐workers reported the first dinuclear platinum metallacyclyne and its single‐crystal structure . Castellano and co‐workers investigated the photophysical properties of discrete platinum(II) metallacycles . The emergence of discrete triangular bipyridine platinum(II) metallacycles and the study of their structures and photophysical properties have provided insights for the investigation of their supramolecular self‐assembly properties utilizing the large planar metallacycles ,.…”
Section: Introductionmentioning
confidence: 99%
“…Castellano and co‐workers investigated the photophysical properties of discrete platinum(II) metallacycles . The emergence of discrete triangular bipyridine platinum(II) metallacycles and the study of their structures and photophysical properties have provided insights for the investigation of their supramolecular self‐assembly properties utilizing the large planar metallacycles ,. Herein, we report a series of alkynylbipyridine platinum(II) complexes ( 1 – 5 ) with different triangular metallacycles and alkyl/oligoether chains (Scheme ).…”
Section: Introductionmentioning
confidence: 99%